Distribution Characteristics and Genesis of Marine Anoxic Conditions in the Southwest of the Upper Yangtze Basin During the Late Ordovician–Early Silurian, South China - Dong, Zaitian; Wang, Zetang; Zhang, Wenli; Cheng, Shaoning; Fu, Xuehai; Wang, Chaoyong (Frontiers in Earth Science, 2022)
The distribution characteristics and formation of marine anoxic conditions through the Late Ordovician–Early Silurian (O–S) remain poorly resolved despite their importance in the preservation of sedimentary organic matter and the formation of black shale. In this study, the major, trace, and pyrite δ34S (δ34Spy) contents of 36 shale samples at the edge of the southwest depocenter of the Upper Yangtze Basin (Tianlin and Changhebian sections) were analyzed to understand the redox conditions, terrigenous clastic inputs, and primary productivity changes. The iron speciation and enrichment factor of U and Mo show that the range of anoxic conditions gradually expanded from the sedimentation center to the edge during the late Katian stage, peaked in the early Hirnantian stage followed by a rapid decrease, and expanded again during the early Rhuddanian stage. Comprehensive index analysis showed that the increase of terrigenous clastic input and the relative decrease of primary productivity due to tectonism and sea level change controlled the transformation of the water column from anoxic, especially euxinic, to suboxic-oxic conditions. This is reflected in the correlation between paleo-salinity, δ34Spy, chemical index of alteration, and the organic carbon accumulation rate. This work emphasizes the control of terrigenous clastic input and sulfate availability on the transformation of marine redox conditions during the O-S period in semi-restricted basins.